(untitled) (Research, Society and Development, 2020)
The aim of this work was to evaluate the water stress in jabuticaba seedlings by flooding the plants for different periods and water depths slide. Two experiments with jaboticaba trees seedlings were installed, in the first, the seedlings aged 18 months were submitted to a 5 cm water slide, for a period of 0, 3, 5, 10 and 15 days or for two periods of 3, 5, 10 and 15 days after a 30-day interval. In the second experiment, the seedlings at 24 months were flooded with water until the height of the colon, for periods of 0, 5, 10 and 15 days, or for two periods of 5, 10 and 15 days after a 30-day interval. Such conditions aim to represent water stress due to flooding. Biometric variables such as number of leaves, stem diameter, total size, dry weight of roots and shoots and total dry matter were evaluated. The physiological determinations were total chlorophyll content and quantum yield. The biochemical variables were protein content, total sugar content, total phenols and proline. The growth of jabuticaba trees was not affected by the flood periods adopted for experiments with different field capacities. In the treatments in which the plants were subjected to the two water cycle flooding, the height of the stem showed significant differences in the increase in number of leaves, height of the seedling and diameter of the stem, which consequently altered the dry mass of the aerial part.